THE LINEAR GROWTH OF ROACH INFECTED WITH LIGULA INTESTINALIS PLEROCERCOIDS IN THE CHIVYRKUYSKY BAY OF THE LAKE BAIKAL - Z. N. Dugarov; Z. A. Rinchinov (Российский паразитологический журнал, 2016)
Objective of research: The purpose of the study is to investigate the influence of Ligula intestinalis plerocercoids on linear growth of roach Rutilus rutilus in the Chivyrkuysky bay of thelakeBaikal.Materials and methods. Roach was caught on a permanent station in the Monakhovo creek of Chivyrkuysky bay of thelakeBaikal at the same time interval (June 25-July 5) in 1997-2005. The analysis of roach infection with L. intestinalis plerocercoids was performed based on incomplete parasitological dissections of 807 host specimens at the age of 0+ to 10+. Standard body length (the distance from the tip of the snout to the anterior end of the caudal fin) was used to characterize the linear growth of roach.Results and discussion. L. intestinalis plerocercoids wasn’t found out in underyearlings (0+) of roach. The host began to be infected with this tapeworm at the age of 1+. The maximum infection level with L. intestinalis plerocercoids was observed in roach at the age of 3+. That one was significantly reduced in the age of 4+. The infection level of roach with L. intestinalis continued to decrease in the next age groups, going down to a minimum at the age of 7+. The roach wasn’t infected with this tapeworm at the age of 8+–10+. A significant reduction of the infection level in the roach in the age classes 4+ and older after the maximum at the age of 3+ was probably associated with parasite-induced mortality of the host during the growth of the age group 3+ to 4+. A standard body length of roach specimens infected with L. intestinalis at the age of 1+ and 2+ was greater than that of uninfected ones. In contrast, the standard body length of the roach specimens infected with this tapeworm was less than that of uninfected ones in subsequent age classes (3 + -6 +). Differences of standard body length between roach specimens infected with L. intestinalis and uninfected ones were statistically significant in the above-mentioned age groups (1 + 6 +). The effect of L. intestinalis plerocercoids on the linear growth of the roach in Chivyrkuysky Bay of the lake Baikal was manifested in an increase of body length of infected host specimens compared to uninfected ones in young age groups (1+ and 2+) and, vice versa, in one’s decrease in age groups 3+–6 +. We proposed to call this effect "reversive".